Thermodynamics - Fermi, Enrico, 1901-1954 (Dover Publications, 1956)
In this classic of modern science, the Nobel Laureate presents a clear treatment of systems, the First and Second Laws of Thermodynamics, entropy, thermodynamic potentials, and much more. Calculus required.
Includes index.
"An unabridged and unaltered republication of the work originally published by Prentice-Hall Company in 1937"--Title page verso.
Keywords: Thermodynamics.; elektronické knihy; electronic books